2011
DOI: 10.1091/mbc.e10-09-0740
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-nonspecific alkaline phosphatase promotes axonal growth of hippocampal neurons

Abstract: A reduction in extracellular ATP levels by TNAP is essential for the development of neuritic processes by cultured hippocampal neurons. Results demonstrate that TNAP-mediated effects regulate both ligand availability and protein expression of P2X7 receptor in the axonal growth cone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 48 publications
3
78
0
2
Order By: Relevance
“…In this sense, the different ectonucleotidase families that modify the number of phosphates in adenine nucleotides could be important regulators (Langer et al, 2008). For example, expression in cultured neurons of tissue non-specific alkaline phosphatase (TNAP), which reduces extracellular ATP levels, improves axonal growth (Diez-Zaera et al, 2011). Our results suggest that axon elongation is regulated through the coordination of the ionotropic ATP-gated P2X7 receptor and ADP-activated P2Y receptors.…”
Section: Discussionmentioning
confidence: 83%
“…In this sense, the different ectonucleotidase families that modify the number of phosphates in adenine nucleotides could be important regulators (Langer et al, 2008). For example, expression in cultured neurons of tissue non-specific alkaline phosphatase (TNAP), which reduces extracellular ATP levels, improves axonal growth (Diez-Zaera et al, 2011). Our results suggest that axon elongation is regulated through the coordination of the ionotropic ATP-gated P2X7 receptor and ADP-activated P2Y receptors.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, inhibiting the P2X7 receptor reduced TNAP expression, whereas the addition of AP enhanced P2X7 receptor expression. The results suggested that TNAP, by regulating both ligand availability and protein expression of P2X7 receptors, is important for axonal development [517]. TNAP was also found to be essential for the differentiation of cultured adult neural stem cells into neurons or oligodendrocytes.…”
Section: Downstream Signalingmentioning
confidence: 97%
“…To date, the functional involvement of APs in purinergic signaling has received rather little attention. An involvement in purinergic signaling has been implicated for TNAP in NG108-15 neuronal cells [515], in human airways [464,516], in bone remodeling [24], and in the control of axon outgrowth in cultured hippocampal neurons [517].…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 99%
“…P2X7 receptors could also be involved in neuronal development. Both the P2X7 receptor and the ectoenzyme tissuenonspecific alkaline phosphatase are expressed in mouse hippocampal neurons at early stages of differentiation, thereby controlling, in a coordinated way, the elongation of the growth cone (Díez-Zaera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%